Malaysian and Australian students’ views on diversity: a differential item functioning analysis - Ssekamanya, Siraje Abdallah; Brown, Jac; Sutton, Jeanna; Badrasawi, Kamal J I; Abu Kassim, Noor Lide (2014)
Background: With global travel and access to media from around the world, people are increasingly confronted with similarities and differences between themselves and others that may encourage building bridges as well as walls. Often reality is distorted fuelling misunderstandings and resentments which sometimes lead to devastating consequences. For example, much of the distrust and violence that is seen in the world is in part, fuelled by perceived differences. Thus, the concept of diversity and people’s attitudes towards it may be a crucial predictor of conflict. Objective: This paper aims to explore the differences and similarities between Malaysian and Australian university students on factors related to their attitudes towards diversity, including level of aggression, nationalism, socialization, and patriotism. Method: A survey was administered to students at the International Islamic University of Malaysia (n=398) and students at the University of Western Sydney (n=239). The Rasch Measurement Model was utilized to investigate the differential item functioning (DIF) across the two nationalities. Results: The analysis showed significant and substantial differences between Australian and Malaysian students on many items related to the different aspects of diversity. DIF contrast favoured Australian students on some items and vice-versa. Results of the DIF analysis support a general view of the two groups. More interestingly, the DIF analysis seems to point to a changing trend among young Malaysians. Conclusion: To explore the factors that relate to attitudes towards diversity is important to understand how these attitudes are formed and how they evolve.